2024
DOI: 10.7150/ntno.87536
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Nanocomposite of ZnS(Mn) Quantum Dots Immobilized Graphene Oxide for Bioimaging Applications

Pavithra Kurungottu,
Midhun Ben Thomas,
Mahesh M Lalitha
et al.

Abstract: Developing a biocompatible and biodegradable graphene-based fluorescent nanoprobe with the ability to visualize live cells could be interesting for intracellular imaging and monitoring the efficiency of chemotherapy. Herein, we report a biodegradable and biocompatible hybrid fluorescent graphene oxide (GO)-ZnS(Mn) composite synthesized via in situ growth of ZnS(Mn) quantum dots (QDs) on the surface of GO in the aqueous medium. The prepared 'GO-ZnS(Mn)' composite was characterized by X-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…It exhibited strong visible light fluorescence and excellent biocompatibility in HeLa cell lines, even at higher concentrations. Confocal fluorescence microscopy demonstrated effective cellular uptake via receptor-mediated endocytosis within 12 h. Biodegradability studies with human myeloperoxidase enzymes confirmed degradation within 15 h, indicating its potential for biomedical applications …”
Section: Properties Of 2d Nanomaterials Used In Healthcare Applicationsmentioning
confidence: 90%
See 1 more Smart Citation
“…It exhibited strong visible light fluorescence and excellent biocompatibility in HeLa cell lines, even at higher concentrations. Confocal fluorescence microscopy demonstrated effective cellular uptake via receptor-mediated endocytosis within 12 h. Biodegradability studies with human myeloperoxidase enzymes confirmed degradation within 15 h, indicating its potential for biomedical applications …”
Section: Properties Of 2d Nanomaterials Used In Healthcare Applicationsmentioning
confidence: 90%
“…Confocal fluorescence microscopy demonstrated effective cellular uptake via receptor-mediated endocytosis within 12 h. Biodegradability studies with human myeloperoxidase enzymes confirmed degradation within 15 h, indicating its potential for biomedical applications. 177 Hydrogels reinforced with oxidized few-layer graphene (GO) demonstrated slower degradation compared to hydrogels without GO in vivo studies. Despite the degradation process, no signs of inflammation or infection were observed at the implantation sites, indicating good biocompatibility.…”
Section: Healthcare Applicationsmentioning
confidence: 99%